Complete mitochondrial genomes of the two Glycyphagoidea mites Lepidoglyphus destructor and Gohieria fusca (Acari: Sarcoptiformes, Glycyphagoidea): Revelation of a novel feature of the largest non-coding region. (September 2021) - Fang, Yu; Xu, Jiaoyang; Zhan, Xuebing; Fang, Weixi; Dong, Fangyuan; Su, Xuan; Chu, Lingmiao; Feng, Rui; Fang, Ying; Zuo, Zetao; Liu, Fei; Xia, Xingquan; et al.
Abstract: Mitochondrial genomes (mitogenomes) of metazoans typically contain 37 genes, comprising 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. To date, complete mitogenome sequences of 15 species of Astigmatina have been elucidated; and they contain variations in several features, such as gene order, unconventional tRNA secondary structures, and the number and internal structures of control regions. Here, we sequenced the mitogenomes of Lepidoglyphus destructor and Gohieria fusca, thus representing the first reported complete mitogenome sequence of mite species from the superfamily Glycyphagoidea. In total, 37 mitochondrial genes were identified in both species. The same gene arrangement pattern was found in both species, and this pattern was consistent with that in the possible common ancestor of astigmatid mites. Most tRNAs were highly truncated in both species, which is typical of acariform mites. The largest non-coding region in L. destructor and G. fusca can be divided into two domains based on AT content and stem-loop structures. Domain I has a stem-loop structure; domain II is more AT-rich than domain I and includes several conserved sequences that are also observed in Acaridae and Pyroglyphidae. The largest non-coding region of Acalvolia sp. (Astigmatina, Hemisarcoptoidea) also exhibits similar features. The phylogenetic relationships found in our study are consistent with those identified by previous phylogenetic studies on astigmatid mites. Within Astigmatina, Glycyphagoidea was recovered as a monophyletic group. Highlights: The two Glycyphagoidea mites, L. destructor and G. fusca, were sequenced and annotated for the first time. As typical for acariform mites, most tRNAs were highly truncated in L. destructor and G. fusca . A novel feature of the largest non-coding region of the mitogenome was found in L. destructor, G. fusca, and Acalvolia sp.